2019
DOI: 10.3389/fpsyg.2019.02707
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Emotional Intelligence on Job Burnout and Job Performance: Mediating Effect of Psychological Capital

Abstract: How does emotional intelligence (EI) affect job performance and job burnout? Direct or indirect? What role does psychological capital play? This study surveyed 450 employees of various enterprises through questionnaires. Results are as follows: (1) Employees' EI has a positive predictive effect on psychological capital and job performance, and it is negatively correlated with job burnout; (2) psychological capital has a negative predictive effect on job burnout and a positive predictive effect on job performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(119 citation statements)
references
References 57 publications
1
79
0
10
Order By: Relevance
“…Based on the literature, six main domains are associated with increased burnout risk: high workload, lack of control, want of reward, need for sense of community, low fairness, and different values [17]. Job burnout is a frequent issue in companies and institutions, and often occurs in high-pressure environments [18]. Furthermore, quantitative job demands such as a high workload experienced and pressurised deadlines are consistently linked to burnout, just as qualitative job demands such as role conflict and role ambiguity [16] or the absence of rewards or emotional recognition [19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, six main domains are associated with increased burnout risk: high workload, lack of control, want of reward, need for sense of community, low fairness, and different values [17]. Job burnout is a frequent issue in companies and institutions, and often occurs in high-pressure environments [18]. Furthermore, quantitative job demands such as a high workload experienced and pressurised deadlines are consistently linked to burnout, just as qualitative job demands such as role conflict and role ambiguity [16] or the absence of rewards or emotional recognition [19].…”
Section: Introductionmentioning
confidence: 99%
“…Los resultados apuntan también la capacidad protectora del capital psicológico frente al burnout en el profesorado. Este efecto se ha resaltado en el personal laboral de instituciones públicas y empresas privadas (Gong et al, 2019;León-Pérez et al, 2016;Li, Wu, Li, Chen y Wang, 2019;Youssef-Morgan y Luthans, 2015). Teniendo en cuenta que el burnout es una amenaza para el bienestar y la satisfacción laboral (Atmaca, Rızaoğlu, Türkdoğan y Yaylı, 2020;Mérida-López y Extremera, 2017), se concluye que el desarrollo del capital psicológico podría prevenir la aparición de este síndrome a través de los recursos positivos que lleva asociados (Gong et al, 2019;Li et al, 2019;).…”
Section: Discussionunclassified
“…El desarrollo del PCQ ha permitido evaluar el capital psicológico en personal laboral de organizaciones, relacionándolo con factores laborales positivos como la motivación, la satisfacción, el compromiso, el desempeño y el rendimiento (Avey, Reichard, Luthans, Mhatre, 2011b;Gong, Chen y Wang, 2019;Tisu , Lupșa, Vîrgă y Rusu, 2020;Xi, Xu y Wang, 2020;Ye, Ren, Li y Wang, 2020). También se ha asociado el capital psicológico con la salud del personal laboral y con bajos niveles de estrés crónico o burnout (Avey et al, 2011b;Gong et al, 2019). Además, se ha propuesto que el liderazgo del personal de dirección, el clima organizacional positivo y ciertos rasgos de personalidad del personal laboral podrían actuar como antecedentes que predicen el desarrollo del capital psicológico (Luthans y Youssef-Morgan, 2017).…”
unclassified
“…PsyCap can be classified as an emotional resource (Yin et al, 2018), and trait EI has been shown to promote the formation of positive strengths such as self-efficacy, hope, resilience, and optimism Di Fabio & Saklofske, 2018;Gong, Chen, & Wang, 2019). For example, people high in trait EI should be more capable of managing emotions positively so as to stay optimistic and hopeful about the future.…”
Section: Emotional Intelligence and Sustainabilitymentioning
confidence: 99%
“…Thus, the optimisation of trait EI in employees should help to improve their psychological capital, and high psychological capital leads to sustainable work behaviours, e.g. positive job performance and less job burnout (Gong, Chen, & Wang, 2019).…”
Section: Emotional Intelligence and Sustainabilitymentioning
confidence: 99%